Huntt for 'King of Swing' closes in: TM Golf's sixth and seventh legs conclude with great success, bringing the much-anticipated grand final that much closer - Golf, Par (Par Golf, 2012)
The sixth leg of Telekom Malaysia Berhad's (TM) TM Golf 2012, which attracted a turnout of 111 golfers, wrapped up at Penang Golf Resort on November 3.